Majorant estimates for the percolation threshold of a Bernoulli field on a square lattice - Virchenko, Yu. P.; Tolmacheva, Yu. A. (Ukrains’kyi Matematychnyi Zhurnal, 2005)
We suggest a method for obtaining a monotonically decreasing sequence of upper bounds of percolation threshold of the Bernoulli random field on Z^2. On the basis of this sequence, we obtain a method of constructing approximations with the guaranteed exactness estimate for a percolation probability. We compute the first term c_2 = 0,74683 of the considered sequence.